Design and development of agricultural drone for precision fertilizer application to optimize crop yields - Amartya Josephat; Aravindkumar Sekar; Deepa T; S. Angalaeswari (Results in Engineering)
In the modern era, precision agriculture has advanced significantly, playing a crucial role in improving crop yields - especially in countries such as India, where more than 70% of the rural population depends on agriculture. Crop losses due to insect and pest-borne diseases remain a major challenge. Traditionally, farmers have relied on pesticides and fertilizers, but manual pesticide spraying poses serious health risks. According to the WHO, approximately one million cases of pesticide-related illnesses occur annually by manual spraying. To address this issue, a customized agri-drone with the adoption of Unmanned Aerial Vehicles (UAVs) is proposed. UAVs significantly reduce health risks and enable precise and efficient pesticide and fertilizer applications. They are especially beneficial in areas where traditional machinery and manual labor face limitations. Equipped with advanced cameras and sensors, drones offer real-time crop monitoring and early disease detection. Beyond spraying, UAVs support crop mapping, irrigation management, and yield forecasting. Their data gathering capabilities improve decision making, resource optimization, and risk mitigation. The integration of drones into agriculture marks a transformational leap, improving pest control, increasing productivity, reducing environmental impact, and protecting farmer health. The proposed drone helps achieve the precise use of fertilizer with an accurate composition of the mixture at minimal cost.